2018
DOI: 10.29328/journal.jpsp.1001018
|View full text |Cite
|
Sign up to set email alerts
|

Control of phytopathogenic microorganisms of post-harvest in tomato (Lycopersicon esculentum Mill.) with the use of citrus extract

Abstract: Diseases are a major cause of post-harvest losses depending on season, region and management practices. Chemical control is the most used but with serious consequences for human health and the environment. This forces us to carry out more exhaustive studies on botanical products. The general objective of the present study was to evaluate the effect of citrus extracts for the control of pathogens that cause post-harvest diseases in tomato fruit. The product to be evaluated is of botanical origin from citrus ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similarly, F. moniliforme, A. niger and R. stolonifer were also isolated from rotten tomato fruits (Onyia et al, 2000). In addition, Lemma et al (2014) [29] [18] , G. Candidum, R. stolonifer, Alternaria sp and Fusarium sp. were the major pathogens causing tomato fruit rots.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, F. moniliforme, A. niger and R. stolonifer were also isolated from rotten tomato fruits (Onyia et al, 2000). In addition, Lemma et al (2014) [29] [18] , G. Candidum, R. stolonifer, Alternaria sp and Fusarium sp. were the major pathogens causing tomato fruit rots.…”
Section: Discussionmentioning
confidence: 99%
“…At temperature 25°C±2 and 45% relative humidity (RH), Cristina et al (2018) tested the effects of citrus extracts on the shelf life of tomatoes. The results showed that under control conditions, the percentage of losses was highest on day 13 and gradually decreased thereafter.…”
Section: Physiological Status Of Fruits and Vegetablesmentioning
confidence: 99%